The Dynamics of Contemporary Fatwas in the Digital Age: A Study of the East Java MUI’s Resistance to the Paylater System - Bhismoadi Tri Wahyu Faizal; Akhmad Farid Mawardi Sufyan; Erie Hariyanto; M. Haris Hidayatulloh; Nashat Mohammad Abdel Qader Bani Hamad (MILRev: Metro Islamic Law Review, 2026)
The East Java MUI Fatwa Number 4 of 2022 on Digital Transactions with the Paylater System emerged amid a national normative vacuum, as the National Sharia Council-Indonesian Ulama Council (DSN-MUI) has yet to issue a fatwa specifically regulating paylater mechanisms. This study aims to analyse: (1) the dynamics of contemporary fatwas in the digital age amid the absence of national Sharia regulation concerning paylater systems; (2) the forms of resistance articulated by the East Java MUI through Fatwa Number 4 of 2022; and (3) the dissemination of the fatwa and its reception among Muslim communities in East Java. This research employs a mixed methods approach integrating normative juridical and empirical perspectives. Primary data were collected through a survey involving 50 respondents across East Java, while secondary data consisted of the fatwa document, relevant DSN-MUI fatwas, academic literature, and media coverage related to digital financial transactions. The findings reveal three principal forms of resistance: resistance to usury (riba) manifested in interest-based charges, resistance to late payment penalties, and resistance to coercive debt collection practices, including intimidation and public shaming. However, this resistance does not amount to an absolute prohibition of paylater systems; rather, it represents a constructive normative critique that opens pathways for the development of Sharia-compliant paylater products. The study further demonstrates that fatwa dissemination remains ineffective, with only 28% of respondents aware of the fatwa’s existence. This research offers a dual contribution. Normatively, it formulates Sharia compliance criteria applicable to paylater mechanisms in the absence of a dedicated DSN-MUI fatwa. Empirically, it provides the first survey-based evidence regarding public awareness and reception of contemporary fatwas within the context of digital Islamic consumer finance governance.